Design and User Experience Evaluation of Bersii Android-based Mobile Application User Interface - Mirza Ramadhani; Achmad Aqil Susanto; Fauzan Mustofa; Viana Salsabila Tauda (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2022)
The user interface has a substantial and influential role because it becomes a direct liaison between the application system and its users and shapes each user's perception of the Bersii application. Bersii application is created to reduce single-use plastic waste in Indonesia to build and increase public awareness of the importance of protecting the environment. The Bersii mobile application has features such as product refills to reduce the use of plastic waste. This paper designs the user interface (UI) of the Bersii mobile application for buying refill products. The user interface (UI) design results will be tested using usability and User Experience (UX). The usability test uses the System Usability Scale (SUS), and the UX test uses the User Experience Questionnaire (UEQ). The results of usability testing obtained a score of 79, which was included in the category “good". In each aspect of the UEQ test, it obtained the following scores:  attractiveness 2,11, perspicuity 1,71, efficiency 1,98, dependability 1,89, stimulation 2,01, and novelty 1,45. Overall, the results of the UEQ testing were included in the category "good”.